Highly Conformal Craniospinal Radiotherapy Techniques Can Underdose the Cranial Clinical Target Volume if Leptomeningeal Extension through Skull Base Exit Foramina is not Contoured. Issue 7 (July 2017) - Noble, D.J.; Ajithkumar, T.; Lambert, J.; Gleeson, I.; Williams, M.V.; Jefferies, S.J.
Abstract: Aims: Craniospinal irradiation (CSI) remains a crucial treatment for patients with medulloblastoma. There is uncertainty about how to manage meningeal surfaces and cerebrospinal fluid (CSF) that follows cranial nerves exiting skull base foramina. The purpose of this study was to assess plan quality and dose coverage of posterior cranial fossa foramina with both photon and proton therapy. Materials and methods: We analysed the radiotherapy plans of seven patients treated with CSI for medulloblastoma and primitive neuro-ectodermal tumours and three with ependymoma (total n  = 10). Four had been treated with a field-based technique and six with TomoTherapy™. The internal acoustic meatus (IAM), jugular foramen (JF) and hypoglossal canal (HC) were contoured and added to the original treatment clinical target volume (Plan_CTV) to create a Test_CTV. This was grown to a test planning target volume (Test_PTV) for comparison with a Plan_PTV. Using Plan_CTV and Plan_PTV, proton plans were generated for all 10 cases. The following dosimetry data were recorded: conformity (dice similarity coefficient) and homogeneity index (D2  − D98 /D50 ) as well as median and maximum dose (D2% ) to Plan_PTV, V95% and minimum dose (D99.9% ) to Plan_CTV and Test_CTV and Plan_PTV and Test_PTV, V95% and minimum dose (D98% ) to foramina PTVs. Results: Proton and TomoTherapy™ plans were more conformal (0.87, 0.86) and homogeneous (0.07, 0.04) than field-photon plans (0.79, 0.17). However, field-photon plans covered the IAM, JF and HC PTVs better than proton plans ( P  = 0.002, 0.004, 0.003, respectively). TomoTherapy™ plans covered the IAM and JF better than proton plans ( P  = 0.000, 0.002, respectively) but the result for the HC was not significant. Adding foramen CTVs/PTVs made no difference for field plans. The mean Dmin dropped 3.4% from Plan_PTV to Test_PTV for TomoTherapy™ (not significant) and 14.8% for protons ( P  = 0.001). Conclusions: Highly conformal CSI techniques may underdose meninges and CSF in the dural reflections of posterior fossa cranial nerves unless these structures are specifically included in the CTV. Highlights: Highly conformal techniques can deliver craniospinal radiotherapy for medulloblastoma. Meninges and cerebrospinal fluid extend through the skull base with cranial nerves. These structures receive inadequate dose if they are not specifically contoured. Posterior fossa foramina should be included in the craniospinal clinical target volume.